Bibliometric Analysis of Earthquake Technologies in Physics Education for Education for Sustainable Development - Hanan Zaki Alhusni; Binar Kurnia Prahani; Titin Sunarti; Madlazim Madlazim; Salma Hasna Hamiydah (Journal of Law and Bibliometrics Studies, 2025)
Objective: This study aims to explore the intersection of earthquake technologies, physics education, and Education for Sustainable Development (ESD) through bibliometric analysis. The objectives include mapping the existing literature, identifying key trends, gaps, and influential publications, and highlighting the contributions of top authors and geographical hotspots in this interdisciplinary field. Method: A comprehensive bibliometric analysis was conducted using publications from 2021 to 2025, sourced from databases like Scopus. Keywords related to earthquake technologies, physics education, and ESD were employed to gather articles. The study utilized tools like VOSviewer and Bibliometrix for citation analysis, co-authorship patterns, and thematic evolution, allowing for the identification of key research trends and collaborations. Results: The analysis reveals a growing body of research, particularly in Asia, with a focus on specific technologies like virtual reality simulations and mobile applications for disaster preparedness. However, the study also highlights a fragmentation in the field, with limited holistic approaches that bridge these technologies and educational frameworks. The most influential authors include Deng X and Xu D, with significant contributions from countries like China, Indonesia, and Japan. Novelty: This study provides a unique bibliometric overview of the intersection between earthquake technologies, physics education, and ESD, a topic not extensively covered in recent literature. It offers new insights into the state of research, identifies key gaps, and lays the foundation for future research in integrating technological innovations into disaster preparedness and education for sustainable development.